The Effects of Using Flashcard Learning Media to Improve Reading Comprehension in Children with Dyslexia - Menik Tetha Agustina; Shofwatun Amaliyah; Maria Dimitrij Angie Pavita (Universitas PGRI Semarang, 2023)
Dyslexia is a specific learning disability characterized by difficulties in reading. This study aims to examine the effectiveness of flashcard learning media in improving reading comprehension between ages 8 and 11 in the group of children identified with dyslexia. The current research used one group experimental design with five children as participants. Based on the results of the study, showed that there was an influence of flashcard learning media on improving the reading ability of dyslexic children. The results of data analysis using t-test showed that the post-test score (M=20,8) was significantly higher than the pre-test score (M=10,4). Analyses of the whole sample indicated that levels of reading comprehension had improved. The finding of this study could be discussed that using flashcard learning media had a positive effect on reading comprehension in dyslexia children. The Flashcard media were designed to be colourful and easy to understand could stimulate children’s willingness to learn and read.